Global business : connecting theory to reality / Yongsun Paik, Dong Chen, William Newburry, and Dan Prud'homme. - Paik, Yongsun; Chen, Dong, 1974-; Newburry, William, 1964-; Prud'homme, Dan (Routledge, 2026)
This textbook is designed to help students recognise and analyse key issues in global business by bridging theory with real world applications. Divided into three parts, it explores critical aspects of global business through about 40 case studies. New and updated case studies illustrate the magnitude and complexity of global business.